Clinical breast examination and its associated factors among reproductive age women in Ghana: multilevel logistic regression analysis - Abebe Gebreegziabher, Zenebe; Semagn, Birhan Ewunu; Walle, Agmasie Damtew; Belay, Mahider Awoke; Wondie, Wubet Tazeb; Degefaw, Gezahagn Demsu; Tilahun, Werkneh Melkie; Melaku, Ermiyas Endewunet; Dejene, Tadesse Mamo (Frontiers in Oncology, 2024)
BackgroundBreast cancer poses a significant health burden in Ghana and globally, being the primary cause of cancer-related illness and death among women. The World Health Organization has identified clinical breast examination as the gold standard for women in low and middle-income countries. However, the uptake of clinical breast examination remains low in these settings, including Ghana, where the nationwide prevalence and associated factors of this practice have not been determined. Therefore, this study aimed to assess the prevalence and factors associated with clinical breast examination among women of reproductive age in Ghana, using data from 2022 Ghanaian Demographic and Health Survey.MethodsIn this study, data from the most recent Ghanaian Demographic Health Survey conducted in 2022 were utilized. The survey used a two-stage stratified sampling technique, and a weighted sample of 15,013 participants was included in the analysis. Descriptive statistics, such as frequencies, percentages, and graphical representations, were utilized to present the study’s findings. Multilevel mixed-effects logistic regression analysis was employed to identify factors associated with clinical breast examination.ResultsThe study found that the prevalence of clinical breast examination was 18.39% (95% CI: 17.8-19.0%). Age group of 45 to 49 (AOR=2.84, 95% CI: 2.13, 3.78), having completed secondary education (AOR=1.70, 95% CI: 1.41, 2.06), having diploma or above education (AOR=3.63, 95% CI: 2.86, 4.61), using modern contraception (AOR=1.12, 95% CI: 1.00, 1.25), having health insurance coverage (AOR=1.53, 95% CI: 1.24, 1.89), listening to the radio at least once per week (AOR=1.35, 95% CI: 1.20, 1.53), reading a newspaper at least once per week (AOR=1.75, 95% CI: 1.39, 2.21), being tested for HIV (AOR=1.92, 95% CI: 1.68, 2.19), undergoing screening for cervical cancer (AOR=6.64, 95% CI: 5.51, 7.99), being currently employed (AOR=1.17, 95% CI: 1.02, 1.34), visiting a health facility within the past 12 months (AOR=1.36, 95% CI: 1.23, 1.51), belonging to the wealthiest wealth categories (AOR=1.70, 95% CI: 1.27, 2.28), being from the North East region (AOR=1.96, 95% CI: 1.19, 3.22) or Oti region (AOR=0.54, 95% CI: 0.34, 0.92), having a greater distance to a health facility (AOR=0.86, 95% CI: 0.75, 0.98), and being from a community with a higher proportion of educated individuals (AOR=1.31, 95% CI: 1.07, 1.61) were significant associated factors of clinical breast examination.Conclusions and recommendationsThe study revealed that the magnitude of clinical breast examination among Ghanaian women was low. Age, educational status, modern contraceptives utilization, health insurance coverage, media exposure, HIV testing, cervical cancer screening, occupation, health facility visits, wealth index, and region were significantly associated with clinical breast examination. These findings suggest that public health interventions should prioritize addressing these factors to increase clinical breast examination uptake and promote early detection of breast cancer to improve the survival of women with breast cancer.